Special designed routing device to ease endoscopic transforaminal lumbar disc surgery: A cadaveric study - Göker, Burcu; Tahta, Alican; Yörükoğlu, Ali; Akçakaya, Mehmet; Şencan, Fahir; Aydoseli, Aydın; Sencer, Altay; Kırış, Talat; Canbolat, Ali (My University, 2019)
Background Data: Fully endoscopic lumbar disc (FELD) surgery via transforaminal (TF) approach may be more demanding to adopt for surgeons experienced with conventional microdiscectomy, due to the necessity of a new anatomic orientation and understanding. We designed a routing device to facilitate access to safe anatomic triangle defined by Kambin at the level of foramen in cadavers. Purpose: To show that the transforaminal route for endoscopic lumbar disc herniations is safely applicable with the aid of a new routing device. Materials and Methods: Ten cadavers between the ages 18-75, with no history of lumbar spinal surgery or trauma, with previous abdominal computed tomography (CT) scans included in our study. Postmortem abdominal CT scans were performed. Images were examined and transforaminal entrance angles without causing damage to retroperitoneal structures for each lumbar disc space and anatomical differences were recorded. TF approach was performed in cadavers using the angles measured from abdominal CTs and the entry point determined with the help of routing device. Results: L1-L2, L2-L3, L3-L4, L4-L5 disc spaces were operated in ten cadavers. Kambin’s triangle was successfully reached with help of routing device using data obtained from CT (X’, ?) and C-arm fluoroscopy (X, Y, Y’). Y’ marker with protractor on routing device, and the metal rod on this Y’ marker with an opening through which only the punction needle could pass were very important in reaching the target. The metal bar horizontal movement and fixation to this mechanism contributed to operation of device. Entrance points and angles calculated with the help of CT scans were found to be compatible with the images obtained from fluoroscopy and endoscopy during operation. Conclusions: In this study, it has been showed that TF approach can be safely performed with help of the new designed routing device.
Keywords: Spinal Endoscopy; Transforaminal; Minimal Invasive Spine Surgery; Exiting Root; Traversing Root; Endoscopic Anatomy